Building the Integrity Fortress: A Holistic Performance Management and Accountability Model for Islamic Educational Institutions - Muhammad Halomoan; Husaini; Elidawati; Rahmat Hidayat (Journal of Education and Teaching Learning, 2026)
Islamic educational institutions are currently facing an accountability crisis and the phenomenon of a "simulacrum of compliance" dominated by secular administrative instruments. The failure of conventional managerial paradigms highlights the urgent need to reconstruct a holistic performance management model. This study aims to formulate an integrated model through four main pillars: Qalbu (intuitive control), Religion (theological foundation), Culture (social control), and Law (formal regulation). Using a Systematic Literature Review (SLR) based on PRISMA 2020 guidelines, 28 key publications from Scopus, Web of Science, and Sinta (2017–2026) were analyzed thematically. The review indicates that the pillars of Qalbu (muraqabah) and Religion serve as the foundation for internal control, mitigating the risk of moral deviation, while Culture (peer control) and Law (Islamic Boarding School Law 18/2019, e-RKAM) act as instruments for enforcing external collective standards. This research proposes "The Integrity Fortress," a conceptual model that synergizes vertical (transcendental) and horizontal (socio-structural) value flows. As a practical output, this model includes an implementation design matrix tailored for Madrasah Aliyah. The design features concrete applications ranging from "Unsupervised Classrooms" to internalizing Qalbu values to the utilization of the e-Madrasah system for legal certainty, illustrated through a governance scenario for student organization funds (OSIM). In conclusion, accountability in Islamic education requires an interlocking ecosystem where spiritual consciousness is transformed into organizational culture and subsequently formalized within the legal system.